The "SHRed Injuries Basketball" neuromuscular training warm-up program reduces ankle and knee injury rates by 36% in youth basketball - Emery, C. A.; Owoeye, O. B. A.; Räisänen, A. M.; Befus, K.; Hubkarao, T.; Palacios-Derflingher, L.; Pasanen, K. (Journal of Orthopaedic & Sports Physical Therapy, 2022)
Objective: To evaluate the effectiveness of a neuromuscular training warm-up prevention program, Surveillance in High school and community sport to Reduce (SHRed) Injuries Basketball, for reducing all-complaint ankle and knee injuries in youth basketball players. Design: Quasi-experimental study. Methods: High school/club basketball teams (male and female players aged 11-18 years) in Calgary, Canada participated in 2016-2017 (control; season 1) and 2017-2018 (intervention; season 2). The control season included a standard-of-practice warm-up. In season 2, a SHRed Injuries Basketball coach workshop was completed by participating team coaches. Teams were randomized by school/club to an unsupervised or a supervised (weekly supervision by study personnel) implementation of the coach-delivered SHRed Injuries Basketball program. The 10-minute SHRed Injuries Basketball program included 13 exercises (ie, aerobic, agility, strength, balance). All-complaint ankle and knee injuries were collected weekly using validated injury surveillance. Multilevel, multivariable Poisson regression analyses (considering important covariates, clustering by team and individual, and offset by exposure hours) estimated incidence rate ratios (IRRs) by intervention group (season 1 versus season 2) and secondarily considered the control versus completion of the SHRed Injuries Basketball program, unsupervised and supervised. Results: Sixty-three teams (n = 502 players) participated in season 1 and 31 teams (n = 307 players: 143 unsupervised, 164 supervised) participated in season 2. The SHRed Injuries Basketball program was protective against all-complaint knee and ankle injuries (IRR = 0.64; 95% confidence interval [CI]: 0.51, 0.79). Unsupervised (IRR = 0.62; 95% CI: 0.47, 0.83) and supervised (IRR = 0.64; 95% CI: 0.49, 0.85) implementations of the SHRed Injuries Basketball program had similar protective effects. Conclusion: The SHRed Injuries Basketball program was associated with a 36% lower rate of ankle and knee injuries. Neuromuscular training warm-ups are recommended as the minimal standard of practice for injury prevention in youth basketball.